Problematika Pemahaman Nahwu Mahasantri Yayasan Munashoroh Indonesia Pusat Ciputat Tangerang Selatan - Vitri Angelina; Eka Nur Khikmah; Fikri Hamdani Ubaidilah; Kisno Umbar (LUGATUNA: Jurnal Prodi PBA, 2023)
This study aims to describe the problems of understanding nahwu faced by students from the Central Indonesian Munashoroh Foundation. This study uses a descriptive qualitative approach. Data obtained by observation, interviews, and documentation. The results showed that the problem of understanding nahwu experienced by mahasantri at the Indonesian Munashoroh Foundation was caused by two factors, the first was internal factors, which consisted of a lack of interest and motivation for female students to study Arabic, especially nahwu, because they felt that nahwu was difficult. to learn. The lack of understanding of the mahasantri about the nahwu materials taught by the teacher. The external factors include, learning nahwu at the Munashoroh Indonesia Center Foundation is less effective, the methods used by teachers in the nahwu learning process are less interesting and less varied, causing boredom for students when studying nahwu. The influence of the environment and friends also greatly influences whether or not the mahasantri are serious about learning nahwu. Keywords: Learning problems, understanding nahwu, Munashoroh foundation, Mahasantri